The Effects of a Couples‐Based Health Behavior Intervention During Pregnancy on Latino Couples' Dyadic Satisfaction Postpartum. Issue 3 (30th March 2018) - Coop Gordon, Kristina; Roberson, Patricia N. E.; Hughes, Jessica A.; Khaddouma, Alexander M.; Swamy, Geeta K.; Noonan, Devon; Gonzalez, Alicia M.; Fish, Laura; Pollak, Kathryn I.
Abstract : Many couples tend to report steadily decreasing relationship quality following the birth of a child. However, little is known about the postpartum period for Latino couples, a rapidly growing ethnic group who are notably underserved by mental and physical health caregivers in the United States. Thus, this study investigated whether a brief couples' intervention focused on helping couples support each other while increasing healthy behaviors might improve dyadic functioning postpartum. This study presents secondary analyses of data regarding couple functioning from a larger randomized controlled trial with 348 Latino couples to promote smoking cessation. Portions of the intervention taught the couple communication and problem‐solving skills to increase healthy behavior. Couples participated in four face‐to‐face assessments across 1 year starting at the end of the first trimester. Latent growth curve analyses revealed that the treatment group reported an increase in relationship satisfaction and constructive communication after the intervention, which diminished by 1‐year follow‐up, returning couples to their baseline levels of satisfaction. Results suggest that incorporating a brief couple intervention as part of a larger health intervention for Latinos may prevent postpartum decreases in relationship satisfaction.